Análisis de las competencias claves para la industria 4.0: Las competencias para la Industria 4.0. - Mababu Mukiur, Richard (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The main aim of this research is on the one hand to analyse the skills required for the current context of the Fourth Industrial Revolution; and, on the other hand, to examine the strategies used for the development of competences to adapt companies to Industry 4.0. The study sample consisted of 440 managers from a variety of sectors of economic activity. A questionnaire on Industry 4.0 competences was administered. The results show that there are several relevant competences that contribute to the development of Industry 4.0, particularly specific or technical competences, transversal competences, and personal or psychological skills.